ANALISIS KOGNITIF PETANI PADI SAWAH DALAM PENGGUNAAN PUPUK DI DISTRIK PRAFI KABUPATEN MANOKWARI - Nafis Shofiah Utami; Holle, Yolanda; Palinggi, Yunita (Department of Social Economic Agriculture, Faculty of Agriculture, University of Papua, Manokwari, West Papua, Indonesia, 2021)
ABSTRAK Tujuan penelitian ini adalah untuk mengetahui tingkat kognitif serta faktor-faktor yang mempengaruhi petani dalam penggunaan pupuk pada petani padi sawah dalam setiap periode tanam. Penelitian dilakukan di Distirk Prafi kabupaten Manokwari dengan metode pengambilan sampel yang dilakukan secara purposive pada dua kampung yaitu kampung Prafi Mulya dan Kampung Desay dengan total 30 sampel yang terdiri dari 15 sampel petani padi sawah pada masing-masing kampung. Penelitian didasarkan dalam 3 tahapan yaitu saat padi berumur 3-20 hari, 30- 45 hari dan padi berumur 50-65 hari dengan melihat hubungan tingkatan kognitif pada penggunaan pupuk dengan pengalaman bertani, keterlibatan belajar dengan PPL , dan informasi dari media pada setiap periode tanam padi sawah. Analisis data menggunakan tabulasi silang, secara parsial dengan Analisis Rank Spearman dan secara simultan dengan analisis Wilcoxon. Hasil penelitian diperoleh presentase penggunaan pupuk pada umur padi 3-20 hari (84,68 %), umur padi 30- 45 hari (90,99), dan umur padi 50-65 hari (89,01%), semuanya berada pada jenjang pertama yaitu ranah mengetahui yang berarti bahwa petani dapat menyebutkan jenis, takaran, cara, waktu, frekuensi, kandungan dan manfaat penggunaan pupuk pada setiap tahapan penanaman. Hasil uji juga menunjukkan nilai siginifikan rs hitung lebih besar dari rs tabel yang berarti bahwa variabel pengalaman bertani, kegiatan belajar bersama PPL da informasi melalui media memiliki hubungan yang erat dengan tingkat pengetahuan kognitif petani padi sawah. Kata Kunci: Kognitif, Padi, Pupuk. ABSTRACT The purpose of this study was to determine the cognitive level as well as the factors that influence farmers in the use of fertilizers on paddy in the rice paddy in each planting period.The research was conducted in Prafi District, Manokwari Regency with purposive sampling method in two villages, namely Prafi Mulya village and Desay village with a total of 30 samples consisting of 15 samples of rice farmers in each village. The study was based in 3 stages, namely when rice was 3-20 days old, 30-45 days old and rice was 50-65 days old by looking at the relationship between cognitive levels in the use of fertilizers with farming experience, learning involvement with Fileld Agricultural Instructure, and information from the media at each rice paddy planting period in the rice paddy .Data analysis used cross tabulation, partially with Spearman Rank Analysis and simultaneously with Wilcoxon analysis. The results showed that the percentage of fertilizer use at the age of 3-20 days (84.68%), the age of paddy 30-45 days (90.99%), and the age of paddy 50-65 days (89.01%), all were at the the basic level that is the realm of knowing, which means that farmers can mention the type, dose, method, time, frequency, content and benefits of using fertilizer at each stage of planting. The results also show a significant value of the calculated Spearman’s rho (rs) is greater than the critical value from Spearman’s rho (rs) tabel, these findings implied that the variables of farmer experience, learning activities with PPL and information through the media have a close relationship with the level of cognitive knowledge of paddy field farmers. Key words: cognitive, rice paddy, fertilizer